Managing projects financed by funding institutions - Telles, Maria Hortência da Costa; Costa, Stella Regina Reis da (Revista Gestão da Produção Operações e Sistemas, 2008)
Currently, one is aware about technological competence as a strategic key to the economic, social and political developmentof the industrial enterprises and countries where they are set. But it is clear the necessity of government support in financingof research and development projects on the defined areas of the technological and scientific policies. However, the big challengefaced by the institutions that do the scientific and technological research is to develop, introduce and improve a methodologyand a management projects model financed by the government fomentation enterprises that fit the organizationalenvironment and the culture of these institutions. In spite of the amount of literature avaiable about management projectsand some well known models, none fit very well in the reality that interferes with these projects. This is the context that thiswork was proposed through a case study developed in the Scientific and Industrial Metrology Board (Dimci) at the NationalInstitute of Metrology, Normalization and Industrial Quality (Inmetro). It was written after having a diagnosis made out ofthe data obtained from a survey. This survey was based on the activities envolving the projects in the institution, interviewswith the coordinators of the projects, and other public research enterprise, similar to Inmetro. The diagnosis resulted in aproposal for a management model of the projects based on the standardization of the procedures and the controls necessaryto provide the clearness of information about how the projects are being carried out. The aim is not only foster betterresults and the consequent improvement of the quality of population, but also to offer Brazilian products and services theopportunity to compete in the international market.Keywords: Projects management, projects management methodology, Research and technology development institution,projects office.